'An Empire Dock': Place Promotion and the Local Acculturation of Imperial Discourse in 'Britain's Third Port'. (2nd January 2021) - Reeve, Michael
Abstract : This article explores the employment and adaptation of imperial ideas and imagery in the civic performance and presentation of Hull, the East Yorkshire port city, during the late nineteenth and early twentieth centuries. Focusing, in particular, on the opening ceremony of a new dock in June 1914 - organised around the procession of King George V and the Queen-consort Mary - the article contests that imperial discourses were adapted for use in the local context during this period. At a time when the British empire was widely seen to require renewal, following military mistakes in South Africa and growing economic and naval competition with Germany and North America, civic performances such as dock openings provided a means for the presentation of the provincial city to a national and, potentially, international audience. They were also an opportunity to present an image of a still robust and powerful empire. Opening ceremonies provided local political and business elites with a stage for situating the city within the broader structures of empire, conferring, in concert with the approval of the Crown, an association with imperial grandeur and socioeconomic innovation.